2007
DOI: 10.1158/0008-5472.can-06-2030
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pancreatic Cancer Stem Cells

Abstract: Emerging evidence has suggested that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

57
1,940
5
27

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,948 publications
(2,029 citation statements)
references
References 30 publications
57
1,940
5
27
Order By: Relevance
“…Almost 10 years later, the first solid tumor stem cells were identified in breast cancer when it was demonstrated that a subpopulation of cells expressing the CD44 ϩ CD24 Ϫ phenotype could form tumors with as few as 100 cells, whereas tens of thousands of the bulk tumor cells did not do so (2). Since then, cancer stem cells have been characterized in human brain tumors (3) and colon (4,5), head and neck (6), and pancreatic cancers (7).…”
mentioning
confidence: 99%
“…Almost 10 years later, the first solid tumor stem cells were identified in breast cancer when it was demonstrated that a subpopulation of cells expressing the CD44 ϩ CD24 Ϫ phenotype could form tumors with as few as 100 cells, whereas tens of thousands of the bulk tumor cells did not do so (2). Since then, cancer stem cells have been characterized in human brain tumors (3) and colon (4,5), head and neck (6), and pancreatic cancers (7).…”
mentioning
confidence: 99%
“…The earliest evidences of CSCs were reported in a breast cancer 3 and in acute myeloid leukemia. 4 The existence of CSCs was later also reported in neural, 5 colon, 6 pancreatic, 7 head and neck, 8 prostate 9 and other cancers. 10,11 CSCs remain largely resistant to the majority of current anticancer therapeutics (i.e.…”
Section: Introductionmentioning
confidence: 87%
“…Currently, cancer cell subpopulations selectively endowed with tumorigenic potential are operationally defined as CSCs and have been prospectively identified from selected types of human solid cancer, such as breast (5), brain (6,7), colon (8,9), head and neck (10), and pancreatic cancer (11). However, the CSC working model is still being subjected to intense debate (12), and data published on colorectal cancer (CRC) indicate that a subgroup of primary CRC is likely to be negative for the marker currently used for isolation of colorectal CSCs (Co-CSCs) (9).…”
mentioning
confidence: 99%